Pathogen genomic surveillance of typhoidal Salmonella infection in adults and children reveals no association between clinical outcomes and infecting genotypes - Britto, CD; Mathias, S; Bosco, A; Dyson, ZA; Dougan, G; Raveendran, S; Abin, VL; Jose, S; Nagaraj, S; Holt, KE; Pollard, AJ (BioMed Central, 2020)
Background India is endemic for enteric fever, and it is not known whether the variations in clinical manifestations between patients are due to host, environmental or pathogen factors.